Comparative study on different organic acids for promoting Solanum nigrum L. hyperaccumulation of Cd and Pb from the contaminated soil. (September 2021) - Han, Ran; Dai, Huiping; Skuza, Lidia; Wei, Shuhe
Abstract: Organic acids-assisted phytoremediation is a promising strategy to remove metal pollutants from the soil. However, few reports have focused on the mechanisms of organic acids promoting the uptake of heavy metals by hyperaccumulators. In this study, 5 types of organic acids, namely polybasic carboxylic acids, acidic amino acids, acidic plant growth regulators, phosphoric and gluconic acids, were comprehensively investigated the effects on the solubility of Cd and Pb in the soil along with their uptake by Cd hyperaccumulator Solanum nigrum L. The results indicated that the addition of Hydroxyethylidene-1, 1-diphosphonic acid (HEDP) and d -Gluconic acid (D-GA) effectively extracted the most of acid-extractable and some of reducible and oxidizable fractions of Cd and Pb in the soil, with the extraction rates of 64.8% and 34.4% for total Cd and 53.6% and 30.0% for total Pb, respectively. HEDP and D-GA significantly increased the accumulations of Cd (57.1% and 35.0%) and Pb (43.4% and 31.9%) by S. nigrum without the inhibition of its biomass, making the great removal efficiencies of Cd (1.35% and 1.16%) and Pb (0.039% and 0.036%) from the soil. The enhanced phytoremediation efficiency of S. nigrum was due to the increase of the extractable Cd and Pb in the rhizosphere but little changes of soil pH and enzyme activities (catalase and urease). Among all of organic acids, HEDP may be an alternative to EDTA because of its characteristics of environmental friendliness and high efficiency. Graphical abstract: Image 1 Highlights: 17 kinds of organic acids were performed to compare the activation effects on Cd and Pb in the soil. HEDP and D-GA significantly promoted the uptake of Cd and Pb by S. nigrum. HEDP and D-GA into the soil slightly affected pH values and enzyme activities. HEDP and D-GA had the strengthening effects on the extractability of Cd and Pb in the rhizosphere soil.